Terrain-Perception-Free Quadrupedal Spinning Locomotion on Versatile Terrains: Modeling, Analysis, and Experimental Validation - Zhu, Hongwu; Wang, Dong; Boyd, Nathan; Zhou, Ziyi; Ruan, Lecheng; Zhang, Aidong; Ding, Ning; Zhao, Ye; Luo, Jianwen (Frontiers in Robotics and AI, 2021)
Dynamic quadrupedal locomotion over rough terrains, although revealing remarkable progress over the last few decades, remains a challenging task. Small-scale quadruped robots are adequately flexible and adaptable to traverse numerous uneven terrains, such as slopes and stairs, while moving along its Sagittal direction. However, spinning behaviors on uneven terrain often exhibit position drifts. Motivated by this problem, this study presents an algorithmic method to enable accurate spinning motions over uneven terrain and constrain the spinning radius of the Center of Mass (CoM) to be bounded within a small range so as to minimize the drift risks. A modified spherical foot kinematics representation is proposed to improve the foot kinematic model and rolling dynamics of the quadruped during locomotion. A CoM planner is proposed to generate stable spinning motion based on projected stability margins. Accurate motion tracking is accomplished with Linear Quadratic Regulator (LQR) to bound the position drift during the spinning movement. Hardware experiments are conducted on a small-scale quadruped robot and the effectiveness of the proposed method is verified on flat ground, stairs and slope terrains, respectively.